Heterosis and inbreeding depression in chilli (Capsicum annuum L.) - A V Agalodia, D B Prajapati (Journal of Spices and Aromatic Crops, 2011)
Investigations were carried out at Jagudan (Gujarat) to study the extent of heterosis and inbreeding depression through six generation mean analysis for yield and yield attributing characters in chilli (Capsicum annuum). The magnitude of heterosis and heterobeltiosis was significant in desired direction with moderate to high for green fruit yield, secondary branches, fruit length; high for number of fruits plant-1, ripe/dry fruit weight and seed to pericarp ratio and low for flowering and ripening of fruit. The cross combinations JCh-676 x JCh-659 showed the highest estimate of relative heterosis and heterobeltiosis for dry fruit yield. All the crosses also revealed inbreeding depression for most of the characters. These traits can be improved effectively through pedigree method of selection. In general, the crosses JCh-730 x JCh-725 and JCh-676 x JCh-659 were identified as promising hybrids since they depicted significant heterosis for green and dry fruit yield and its important yield contributing characters.